Edizione, Annotazione, Visualizzazione. Problemi e prospettive della/per la filologia digitale - Paola Italia (Umanistica Digitale)
The essay presents a reflection on the consequences that the massive digitisation of manuscript and printed cultural heritage has had on digital philology and new ecdotic paradigms: from the centrality of the document, which pushes towards a bédierization of editorial models, to the overcoming of the ‘apico-basal’ model towards mixed models, to IIIF annotations, with the two different case studies of the Biblioteca Digitale Vaticana and the Estense Digital Library, which introduce a new model of knowledge sharing, between palaeographic transcription and commentary, particularly suitable in the educational field. The essay concludes with an exploration of the consequences of Data Visualization in the representation of textual phenomena, and its impact on the study of texts and the construction of a ‘textual literacy’, i.e. a textual competence, as an integral part of humanistic education.